ANALISIS SERVUCTION MODEL JASA PENDIDIKAN SD MULIA DHARMA DI PONTIANAK - Arief Hartono (FIRM Journal of Management Studies, 2017)
AbstractMarketing activities are needed in all sectors of business and organizations. Schools which offer education services also need marketing for student intakes that generates revenues for the school. The key to marketing success of a school is the satisfaction of students and their parents, especially Primary School level where parents play an important role in making decision which school to enroll. But customers’ satisfaction doesn’t come automatically, it depends on how the marketers can satisfy their customers. Four factors directly influence service experience of customers : servicescape (physical evidence), contact personnel/service providers, other customers, and organizations and systems. The writer made a study on the servuction model of SD Mulia Dharma in Pontianak using  descriptive method involving the whole population, students and parents, as respondents. It is concluded that most respondents are not satisfied with the school’s servicescape, some teachers’ communication skills, and the Foundation’s low willingness to develop the school. The management of the school is recommended to improve the school’s physical environment, teachers’ communication skills and build communications with the students’ parents represented by Komite Sekolah (School Committee).